Pathways and identity: toward qualitative research careers in child and adolescent psychiatry - Andrés Martin; Madeline DiGiovanni; Amber Acquaye; Matthew Ponticiello; Débora Tseng Chou; Emilio Abelama Neto; Alexandre Michel; Jordan Sibeoni; Marie-Aude Piot; Michel Spodenkiewicz; Laelia Benoit (BMC, 2024)
Abstract Objective Qualitative research methods are based on the analysis of words rather than numbers; they encourage self-reflection on the investigator's part; they are attuned to social interaction and nuance; and they incorporate their subjects' thoughts and feelings as primary sources. Despite appearing well suited for research in child and adolescent psychiatry (CAP), qualitative methods have had relatively minor uptake in the discipline. We conducted a qualitative study of CAPs involved in qualitative research to learn about these investigators' lived experiences, and to identify modifiable factors to promote qualitative methods within the field of youth mental health. Methods We conducted individual, semi-structured 1-h long interviews through Zoom. Using purposive sample, we selected 23 participants drawn from the US (n = 12) and from France (n = 11), and equally divided in each country across seniority level. All participants were current or aspiring CAPs and had published at least one peer-reviewed qualitative article. Ten participants were women (44%). We recorded all interviews digitally and transcribed them for analysis. We coded the transcripts according to the principles of thematic analysis and approached data analysis, interpretation, and conceptualization informed by an interpersonal phenomenological analysis (IPA) framework. Results Through iterative thematic analysis we developed a conceptual model consisting of three domains: (1) Becoming a qualitativist: embracing a different way of knowing (in turn divided into the three themes of priming factors/personal fit; discovering qualitative research; and transitioning in); (2) Being a qualitativist: immersing oneself in a different kind of research (in turn divided into quality: doing qualitative research well; and community: mentors, mentees, and teams); and (3) Nurturing: toward a higher quality future in CAP (in turn divided into current state of qualitative methods in CAP; and advocating for qualitative methods in CAP). For each domain, we go on to propose specific strategies to enhance entry into qualitative careers and research in CAP: (1) Becoming: personalizing the investigator's research focus; balancing inward and outward views; and leveraging practical advantages; (2) Being: seeking epistemological flexibility; moving beyond bibliometrics; and the potential and risks of mixing methods; and (3) Nurturing: invigorating a quality pipeline; and building communities. Conclusions We have identified factors that can support or impede entry into qualitative research among CAPs. Based on these modifiable findings, we propose possible solutions to enhance entry into qualitative methods in CAP (pathways), and to foster longer-term commitment to this type of research (identity).